Novel subcision technique combined with either microneedling or trichloroacetic acid 35% peeling for acne scars: a comparative study - Amira A Zayed; Rasha A Abelghafar; Ahmed I Hehazy; Sarah Orabi; Marwa S El-Mesidy (Wolters Kluwer Medknow Publications, 2021)
Background Challenging treatment of acne scars makes it a must to have a plan for each case specifically. Subcision breaks the fibrous strands tethering the scar but is followed by recurrence. Chemical peeling and microneedling are other treatment options. Objectives To evaluate a new subcision technique combined with either microneedling or peeling in the treatment of acne scars. Patients and methods A total of 20 patients with bilateral rolling and boxcar acne scars were enrolled. Subcision using microkeratomes was done followed by either peeling using 35% trichloroacetic acid on one side or microneedling on the other side. Evaluation of response was done by Echelle d'Evaluation clinique des Cicatrices d'acné grading scale and optical coherence tomography imaging. Results Both therapeutic modalities yielded statistically significant improvement of acne scars and statistically significant decrease in acne scar depth. There was neither a statistically significant difference between the two sides regarding Echelle d'Evaluation clinique des Cicatrices d'acné scoring after treatment (P=0.968) nor regarding optical coherence tomography acne scar depth after treatment (P=0.583). Conclusion This novel technique of subcision is a safe and effective method for rolling and boxcar scar treatment, with almost no adverse effects and no downtime. In addition, trichloroacetic acid 35% peel is cheaper, as well as does not need any extensive special training or expensive instruments, as compared with microneedling, but microneedling shows better skin tightness and improvement of skin elastolysis especially in older patients.